2017
DOI: 10.1088/1361-6382/aa97ff
|View full text |Cite
|
Sign up to set email alerts
|

The fingerprints of black holes—shadows and their degeneracies

Abstract: Abstract. We show that, away from the axis of symmetry, no continuous degeneration exists between the shadows of observers at any point in the exterior region of any Kerr-Newman black hole spacetime of unit mass. Therefore, except possibly for discrete changes, an observer can, by measuring the black holes shadow, determine the angular momentum and the charge of the black hole under observation, as well as the observer's radial position and angle of elevation above the equatorial plane. Furthermore, his/her re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Various related investigations have been carried out by many groups (e.g. [6][7][8][9][10][11][12][13][14][15][16][17]). Although the velocity of the observer can yield aberrational effects, these were found to be negligible for observing the shadow of Sgr A* [18].…”
mentioning
confidence: 99%
“…Various related investigations have been carried out by many groups (e.g. [6][7][8][9][10][11][12][13][14][15][16][17]). Although the velocity of the observer can yield aberrational effects, these were found to be negligible for observing the shadow of Sgr A* [18].…”
mentioning
confidence: 99%
“…Because we do not a priori know the distance between Earth and an observed astrophysical black hole we cannot lift this degeneracy using observations of the shadow alone. Mars, Paganini and Oancea [47] showed that for Kerr-Newman black holes and observer's that are not located on the axis of symmetry this degeneracy is lifted. They also concluded that for Kerr-Newman-NUT black holes the only parameter that cannot be determined from observations of the shadow alone is the gravitomagnetic charge n. However, in this paper we do not consider the spin and therefore we need additional observables that help us to distinguish between the shadows in different spacetimes and to potentially measure the gravitomagnetic charge n.…”
Section: B the Shadowmentioning
confidence: 99%
“…In practice, however, the light emitting astrophysical environment around the BH may cause degeneracies and make very different spacetimes potentially yield similar shadows -see e.g. [21,22] for examples.…”
Section: Introductionmentioning
confidence: 99%